On the ignorance of group-level effects: the tragedy of personnel evaluation? - Sydow, Momme von; Braus, Niels; Hahn, Ulrike (Journal of experimental psychology, 2019)
In social-dilemma situations (e.g., public-good games), people may pursue their local self-interests, thereby lowering the overall payoff of their group and, paradoxically, even their individual payoffs as a result. Likewise, in inner-individual dilemmas, even without conflict of interest between persons, people may pursue local goals at the expense of overall utility. Our experiments investigate such dissociations of individual- and group-level effects in the context of personnel evaluation and selection. Participants were given the role of human resource managers selecting workers to optimize the overall payoff for the company. We investigated contexts where the individually best/worst ‘employees’ systematically caused the worst/best group performance. When workers in a team could substantially increase or decrease coworkers’ performance, most participants (albeit not all) tended to focus solely on individual performance without considering their overall contribution even when instructed to maximize group performance. This undue focus on individual information meant that employees who enhanced team performance the most received the most negative evaluations. This may result in a ‘tragedy of personnel evaluation’ relevant to maladaptive incentive structures (personnel evaluation), job offers (personnel selection), and a substantially negative impact on organizational effectiveness. At the same time, the results suggest ways that this problem may be overcome. (PsycINFO Database Record (c) 2019 APA, all rights reserved)